Risks of Technology-Oblivious Policy. - Simons, Barbara; Horning, Jim (Communications of the ACM, 2005)
The article focuses on the risks of technology-oblivious policy. People who have never written code do not understand how difficult it is to avoid and/or find bugs in software. Therefore, they don't understand why software patches are so dangerous. The Digital Millennium Copyright Act (DMCA), which became law in the U.S. in 1998, is illustrative. The most controversial portions of the DMCA, the anti-circumvention and anti-dissemination provisions, did not come into effect until 2000. It was only by chance that people learned why the delay occurred. The delay was written into the DMCA because lawmakers believed aspects of the DMCA might criminalize work on securing software against Y2K problems. One consequence of the poorly drafted DMCA is that the anti-circumvention provisions can prevent independent experts from inspecting and testing voting machine software to check for bugs and malware without permission. Of course, there are also major differences between the tax code and software. The tax code is relatively small--although it runs to several thousand printed pages, Windows XP has 40 million lines of source code.